Analisis Pembuktian Dalam Sengketa Wanprestasi Perjanjian Jual Beli Tanah - Rahel Rezky Simanjuntak; Muhammad Hafidz Al Ayuda; Najwa Najwa; Viona Ardhanareswari; Zenitri Fayza; Dwi Aryanti Ramadhani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
A land sale and purchase agreement is an important event in everyday life. However, this agreement often experiences problems, such as default. Default is the performance of an obligation that is not on time, resulting in the obligation for the debtor to provide or pay compensation. This article discusses the dispute in Supreme Court Decision No. 12/Pdt.G/2024/PN.Ptk. In this decision, the Plaintiff must pay court costs of Rp. 1,179,000 (one million seventy nine thousand rupiah). This article aims to identify the defaults that occurred and analyze the evidence of the parties in the trial. The research method used in researching this case study is the normative juridical method, which is a legal research method carried out by examining the implementation or implementation of rules in positive law (legislation) and written documents on certain legal events that occur in society. This default was committed by the Defendant, namely Burhanuddin, S.Pd., with the type of default being an act that was not in accordance with the contract. Based on the evidence presented by the parties, the Pontianak Court Judge stated that the defendant's decision was rejected because of the exception, regarding the lack of parties and Error in persona (wrong party) so that the plaintiff was ordered to pay all costs incurred in this case in the amount of Rp. 1,179,000 (one million one hundred seventy nine thousand rupiah).